Physical Test Methods for Elastomers - Brown, Roger (Springer International Publishing : Imprint: Springer, 2018)
This book provides comprehensive coverage of all aspects of physical testing of elastomers (rubbers and thermoplastic elastomers) including mechanical, electrical, thermal and all aspects of durability. Elastomers are an important class of materials used in such products as tyres, seals and hose which have markedly different properties to other materials. The importance of testing of elastomers means that a comprehensive text on the subject is essential. The advantage over general materials testing books is being more specific while the advantage over general rubber technology books is that testing is dealt with in depth. Provides an essential, comprehensive reference on the testing of elastomers; Treats testing methods and considerations more in-depth than most general rubber technology; Critical for the rubber industry, the industries using rubber products, and polymer research.